Effect of a Physical Activity Intervention on the Metabolic Syndrome in Pakistani Immigrant Men: A Randomized Controlled Trial - Andersen, Eivind (Springer US, 2012)
Physical activity (PA) is thought to prevent the metabolic syndrome (MetS), which is prevalent among south Asian immigrants in Western countries. The purpose of this study was to explore whether increasing PA improves the MetS and associated components in a group of Pakistani immigrant men living in Norway. One- hundred and fifty physically inactive Pakistani immigrant men were randomized to either a control group (CG) or an intervention group (IG). The 5 months intervention focused on increasing PA level, which was assessed using accelerometer recordings. Total PA level (counts min(−1)) increased significantly more in the IG than in the CG. The mean difference between the two groups was 49 counts min(−1), which translates into a 15% (95% CI = 8.7% to 21.2%; P = 0.01) greater increase in total PA level in the IG than in the CG. Serum insulin concentration and waist circumference decreased more in the IG compared with the CG. Other MetS related factors and the prevalence of the MetS did not differ between the groups after the intervention. A five- month intervention program can increase PA level and cardiorespiratory fitness, and reduce insulin concentration and waist circumference. However this intervention program may not lower the prevalence of the complete MetS in Pakistani immigrant men.